2011
DOI: 10.1021/ja200212b
|View full text |Cite
|
Sign up to set email alerts
|

Defining the RNA Internal Loops Preferred by Benzimidazole Derivatives via 2D Combinatorial Screening and Computational Analysis

Abstract: RNA is an important therapeutic target, however, RNA targets are generally underexploited due to a lack of understanding of the small molecules that bind RNA and the RNA motifs that bind small molecules. Herein, we describe the identification of the RNA internal loops derived from a 4096-member 3×3 nucleotide loop library that are the most specific and highest affinity binders to a series of four designer, drug-like benzimidazoles. These studies establish a potentially general protocol to define the highest af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
91
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(94 citation statements)
references
References 40 publications
3
91
0
Order By: Relevance
“…Although 3 does not bind to the DNA hairpin (K d > 50,000 nM), 2 binds to this DNA with a K d of 200 nM. Thus, appendage of 2 to 1, a molecule that does not bind DNA because it has bulky t-butyl groups (12,27), ablates the binding of 3 to DNA. Taken together, control of target binding in multivalent ligands depends on the identity of the modules individually and collectively and the distance between them, which has been previously observed (20,28).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although 3 does not bind to the DNA hairpin (K d > 50,000 nM), 2 binds to this DNA with a K d of 200 nM. Thus, appendage of 2 to 1, a molecule that does not bind DNA because it has bulky t-butyl groups (12,27), ablates the binding of 3 to DNA. Taken together, control of target binding in multivalent ligands depends on the identity of the modules individually and collectively and the distance between them, which has been previously observed (20,28).…”
Section: Resultsmentioning
confidence: 99%
“…The database is comprised of privileged interactions identified by a library vs. library screen named 2D combinatorial screening (2DCS) (11,12). In 2DCS, a library of array-immobilized small molecules is probed for binding to a library of small RNA motifs that are likely to be present in biological RNAs (11,12).…”
mentioning
confidence: 99%
“…The authors applied a particularly clever screening methodology called 2D combinatorial screening (2DCS) [65][66][67]. In 2DCS, a small-molecules library is conjugated onto an agarose microarray surface.…”
Section: Focused Screening Approachmentioning
confidence: 99%
“…Velagapudi et al 123 reported a new method called Inforna for sequence-based design of SMIR to target pre-miRs. Inforna integrated a selection-based strategy (Two-Dimensional Combinatorial Screening; 2DCS), 124 a statistical approach (Structure-Activity Relationship through Sequencing; StARTS), 125,126 and the structural information about the RNA target of interest that identified RNA motifs that positively and negatively contributed to binding. After screening and optimization, they selected three compounds for miR-96 precursor, miR-210 precursor, and miR-182 precursor, respectively.…”
Section: Small Molecule Mirna Therapeutic Agentsmentioning
confidence: 99%